2001
DOI: 10.1038/sj.ejcn.1601133
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mortality among whole grain bread eaters in men and women in the Norwegian County Study

Abstract: Objective: To study whether mortality is reduced among whole grain eaters in Norway. Design: Non-interventional, prospective, baseline 1977 ± 1983, followed for mortality through to 1994. Setting: Three Norwegian counties. Subjects: A total of 16 933 men and 16 915 women; systematic screening of all residents aged 35 ± 56 y at baseline, not disabled and free of cardiovascular disease (79% response rate). Predictor variable: We combined self-report of type and number of bread slices (white, light whole grain, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
120
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 16 publications
8
120
0
2
Order By: Relevance
“…This finding is in agreement with other studies regarding smoking and wholegrain consumption conducted inside and outside Norway (3,12,13,29) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in agreement with other studies regarding smoking and wholegrain consumption conducted inside and outside Norway (3,12,13,29) .…”
Section: Discussionsupporting
confidence: 93%
“…Median wholegrain bread consumption was quite high in both consumption groups, and the median intake of partly refined and refined bread was zero in both groups. Others have also found that bread consumption is common among Norwegian women, particularly wholegrain bread (1,3,15) . In Europe it has been reported that consumption of dark bread (which refers primarily to rye and coarse wholegrain bread in the Nordic countries) varies substantially, and that the mean consumption among Norwegian women is high (28) .…”
Section: Discussionmentioning
confidence: 99%
“…After reading the full articles, 22 studies remained that excluded duplicate reports of the same cohort at different periods of followup. Exclusion of a further three reports that included inadequate detail or insufficient range of whole-grain intakes and three non-epidemiological studies resulted in 15 retained reports (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) , two of which related to data not published in full (Good et al (34) was a conference abstract, Thane et al (35) was an Epublication ahead of print at the time of the search and analysis; both sets of authors provided further details as a personal communication). Details of the 15 retained papers containing cross-sectional data or reports of cohorts from which cross-sectional data were extracted are shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Information was presented by gender separately in three papers (32,34,35) , with the result that 20 data pairs were available for analysis representing 119 829 subjects. Table 1 provides details of the main characteristics of the studies including BMI, WC and WHR.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This may outweigh any beneficial effect of grain fiber observed in other populations. Wholegrain intake lowered cardiovascular risk in several studies (Jacobs et al, 1998(Jacobs et al, , 2001Liu et al, 1999), and in the Iowa Women's Health Study cohort whole grain, but not refined grain, was inversely related to all-cause mortality .…”
Section: Fiber and Myocardial Infarctionmentioning
confidence: 95%